1962
DOI: 10.1172/jci104575
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolism of Desmosterol in Human Subjects During Triparanol Administration*

Abstract: Recent studies with triparanol (1-[p-,3-diethylaminoethoxyphenyl ]-1-(p-tolyl) -2-(p-chlorophenyl)ethanol) have demonstrated that this compound inhibits cholesterol biosynthesis by blocking the reduction of 24-dehydrocholesterol (desmosterol) to cholesterol (2-4). Administration of triparanol to laboratory animals and to man results in the accumulation of desmosterol in the plasma and tissues, usually with some concomitant lowering of the plasma total sterol concentration (2, 5). In studies with human subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

1962
1962
1988
1988

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…In our previous study, indirect evidence was presented for the conversion of desmosterol to bile acids and to steroid hormones in triparanoltreated men (2). The present study provides confirmatory direct evidence for this conclusion by in vitro experiments with tissues from triparanoltreated rats and mice.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In our previous study, indirect evidence was presented for the conversion of desmosterol to bile acids and to steroid hormones in triparanoltreated men (2). The present study provides confirmatory direct evidence for this conclusion by in vitro experiments with tissues from triparanoltreated rats and mice.…”
Section: Discussionsupporting
confidence: 86%
“…These results confirm our previous in vivo study (2), which suggested that desmosterol was similar to cholesterol in its ability to serve as a precursor for bile acids and for steroid hormones in patients on triparanol therapy.…”
Section: Marysupporting
confidence: 91%
See 1 more Smart Citation